Investigation of the Structures Properties and Applications of Phosphate Based Glasses - Budi , Agus Setyo; Herawan, Safarudin Gazali; Ayob, Mohd Nizam; Ahmad, Asmala; Lau, Kok Tee (2006)
Glasses based on RO-R20-Na 20-Al20.r-P20 5 (R= Mg, Ca, Ba and RO = Li system has successfully been prepared and their properties and structural features have been investigated. The properties of those glasses seem to depend on the field strength of the alkali or alkali-earth ions in glasses as in silicate glasses The density was determined by means of an ordinary principle of Archimedes and it was found that the density increases as Ro and R20 oxide was introduced replacing some amount of Al203. The spectra of glasses have been studied within the spectral range of 4000 cm-I to 100 cm-1 by Fourier transform infrared spectroscopy. Infrared (JR) spectroscopy indicates that the glass network is dominated by bridging P-tetrahedral present in glasses with O/P = 3.0. The variation in physical properties of the glasses seem to be closely related to the variation in structure of the glasses and could be explained by simple mechanism such as field strength and differences in mass.